Pengaruh Kualitas Produk, Kualitas Layanan, Dan Harga Terhadap Keputusan Pembelian (Study Pada Pelanggan Toko Aneka Sport Di Jl.Kalpataru Kota Malang) - Arman Tijar; Agus Widarko; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this study was to determine the effect of product quality, service quality, and price on purchasing decisions. The independent variables used are product quality, service quality, and price, while the dependent variable is purchasing decisions. The sample used in this study was 75 respondents. Keywords : Product Quality, Service Quality, Price, Purchase Decision